"Show Farmers": Transformation and Performance in Telangana, India. (June 2017) - Flachs, Andrew
Abstract: In this article, I describe a paradoxical but necessary creation of the development apparatus: the "show farmer" (Stone 2014). Various corporate, state, and NGO development projects call upon show farmers to demonstrate the viability of alternative agriculture for visiting funders, scientists, media, and growers. As village gatekeepers, show farmers cultivate local celebrity and publicize a model not just for their community but for the sustainability of agricultural development interventions in the global South generally. This transformation is, however, contingent—when the incentives, ranging from farming infrastructure to social recognition, dry up, show farmers may abandon the stage and development interventions can fail. In addition to qualitative ethnography and interviews, this article draws on 12 months of seed choice and household demographic surveys conducted 2012–2014 among 104 organic cotton farmers in the Warangal and Asifabad districts of Telangana, India. To better understand how alternative agriculture interventions are affecting rural life and how farmers create new avenues for agricultural success through the development apparatus, anthropologists must pay more attention to this crucial but underexplored character.